Differential relationship between physical activity and intake of added sugar and nutrient-dense foods: A cross-sectional analysis. (1st September 2019) - Koehler, Karsten; Boron, Julie B.; Garvin, Teresa M.; Bice, Matthew R.; Stevens, Jeffrey R.
Abstract: A curvilinear relationship exists between physical activity (PA) and dietary energy intake (EI), which is reduced in moderately active when compared to inactive and highly active individuals, but the impact of PA on eating patterns remains poorly understood. Our goal was to establish the relationship between PA and intake of foods with varying energy and nutrient density. Data from the 2009–2010 United States National Health and Nutrition Examination Survey were used to include a Dietary Screener Questionnaire for estimated intakes of added sugar, fruits and vegetables, whole grains, fiber, and dairy. Participants (n = 4766; 49.7% women) were divided into sex-specific quintiles based on their habitual PA. After adjustment for age, body mass index, household income, and education, intakes were compared between PA quartiles, using the lowest activity quintile (Q1) as reference. Women in the second to fourth quintile (Q2-Q4) consumed less added sugar from sugary foods (+2 tsp/day) and from sweetened beverages (+2 tsp/day; all p < 0.05 vs. Q1). In men, added sugar intake was elevated in the highest activity quintile (Q5: +3 ± 1 tsp/day, p = 0.007 vs. Q1). Fruit and vegetable intake increased (women: Q1-Q4 +0.3 ± 0.1 cup eq/day; p < 0.001; men: Q1-Q3 +0.3 ± 0.1 cup eq/day, p = 0.002) and stagnated in higher quintiles. Dairy intake increased with PA only in men (Q5: +0.3 ± 0.1 cup eq/day, p < 0.001 vs. Q1). Results demonstrate a differential relationship between habitual PA and dietary intakes, whereby moderate but not necessarily highest PA levels are associated with reduced added sugar and increased nutrient-dense food consumption. Future research should examine specific mechanisms of food choices at various PA levels to ensure dietary behaviors (i.e., increased sugary food intake) do not negate positive effects of PA. Graphical abstract: Image 1